2018
DOI: 10.1093/mnras/sty1053
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the morphology of supernova remnant (SNR) 1987A with the jittering jets explosion mechanism

Abstract: We find that the remnant of supernova (SN) 1987A shares some morphological features with four supernova remnants (SNRs) that have signatures of shaping by jets, and from that we strengthen the claim that jets played a crucial role in the explosion of SN 1987A. Some of the morphological features appear also in planetary nebulae (PNe) where jets are observed. The clumpy ejecta bring us to support the claim that the jittering jets explosion mechanism can account for the structure of the remnant of SN 1987A, i.e.,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 93 publications
(174 reference statements)
1
10
0
Order By: Relevance
“…This value is far sufficient to explain the energy that has been estimated for jet-like structures seen in nearby supernova remnants, for example the high-velocity, wide-angle NE and SW features seen in Cassiopeia A (e.g., Fesen & Milisavljevic 2016), the faint protrusion or "chimney" that extends out from the northern rim of the visible Crab Nebula (which is often called northern ejecta "jet"; e.g. Gull & Fesen 1982;Blandford et al 1983;Davidson & Fesen 1985;Fesen & Staker 1993;Black & Fesen 2015), and, if these structures are indeed connected to flows originating from the explosion center, also some ear-like extensions that have been interpreted into images of various supernova remnants (Bear et al 2017;Bear & Soker 2018a;perhaps even in SN 1987A, Soker 2021. All of these features might possibly be relics of collimated post-explosion outflows linked to the formation of fallback disks around the new-born neutron stars.…”
Section: Partial Accretion Disks Jetsmentioning
confidence: 99%
See 1 more Smart Citation
“…This value is far sufficient to explain the energy that has been estimated for jet-like structures seen in nearby supernova remnants, for example the high-velocity, wide-angle NE and SW features seen in Cassiopeia A (e.g., Fesen & Milisavljevic 2016), the faint protrusion or "chimney" that extends out from the northern rim of the visible Crab Nebula (which is often called northern ejecta "jet"; e.g. Gull & Fesen 1982;Blandford et al 1983;Davidson & Fesen 1985;Fesen & Staker 1993;Black & Fesen 2015), and, if these structures are indeed connected to flows originating from the explosion center, also some ear-like extensions that have been interpreted into images of various supernova remnants (Bear et al 2017;Bear & Soker 2018a;perhaps even in SN 1987A, Soker 2021. All of these features might possibly be relics of collimated post-explosion outflows linked to the formation of fallback disks around the new-born neutron stars.…”
Section: Partial Accretion Disks Jetsmentioning
confidence: 99%
“…of super-luminous events in the case of significant accretion power (Dexter & Kasen 2013). Morever, a number of pulsars and magnetars have been announced to possess planets or circumstellar disks, and "ears" and asymmetric structures in a larger sample of supernova remnants including SN 1987A have been interpreted as relics of jet-like outflows (Bear et al 2017;Bear & Soker 2018a).…”
Section: Partial Accretion Disks Jetsmentioning
confidence: 99%
“…Larsson et al (2021) mention that the [O III] irregular ring-like structure of SNR 0540-69.3 might be similar to the CO torus expanding with a velocity of 1700 km s −1 that ALMA observations reveal in SNR 1987A (Abellán et al 2017). Bear & Soker (2018b) attributed the shaping of the CO torus in SNR 1987A to jittering jets. I therefore propose here the possibility that the [O III] irregular ring-like structure of SNR 0540-69.3 was compressed by two opposite jets with a jets' axis perpendicular to the plane of the [O III] irregular ring-like structure.…”
Section: A Point-symmetric Morphologymentioning
confidence: 92%
“…Soker (2017) compared the Fe structure of SN 1987A from Larsson et al (2016) with the numerical simulations by Wongwathanarat et al (2015) and concluded that the neutrino-driven explosion mechanism cannot account for the properties of SN 1987A. Bear & Soker (2018b) use the observations of Abellán et al (2017) to compare some morphological features of SN 1987A with morphological features of other SNRs and with plane-tary nebulae, and further argue that jittering jets played a crucial role in the explosion of SN 1987A. I note that the earlier claim of Wang et al (2002) that two opposite non-jittering jets exploded SN 1987a is in conflict with the structure of the ejecta that Abellán et al (2017) reveal (see discussion by Bear & Soker 2018b).…”
Section: Introcutionmentioning
confidence: 99%
See 1 more Smart Citation